(untitled) (Nexus International Journal of Science and Education, 2024)
This research study utilized a quantitative research design, specifically descriptive correlational design, to investigate the relation between leadership behavior and the effectiveness of reading comprehension strategies and interventions. Moreover, the Multiple Regression analysis was employed to measure the influence of leadership-empowering behavior on the effectiveness of reading comprehension strategies and interventions. The study's respondents were the 210 teachers in Cluster 13, Division of Davao City, who were selected through a stratified random sampling technique. Findings revealed that the leadership-empowering behavior of the students in terms of delegation of authority, accountability, self-directed decision-making, information sharing, skill development, and coaching for innovative performance was extensive, thus oftentimes observed. At the same time, the reading comprehension strategies were effective regarding facilities, funding, reading resources support, reading clinic objectives, instructional strategies, assessment techniques, intervention activities, and monitoring and evaluation were extensive, thus oftentimes observed. Likewise, there was a significant relationship between leadership and the effectiveness of reading comprehension strategies. Furthermore, leadership-empowering behavior was a significant predictor of the effectiveness of reading comprehension strategies.